In-depth investigation of thermochemical performance in a heat battery: Cyclic analysis of K2CO3, MgCl2 and Na2S. (1st April 2018) - Sögütoglu, L.C.; Donkers, P.A.J.; Fischer, H.R.; Huinink, H.P.; Adan, O.C.G.
Graphical abstract: Highlights: K2 CO3 is a promising salt for thermochemical heat battery application. 1 m 3 of K2 CO3 can store 15–66 GJ annually, repeated over at least 20 years. CO2 adsorption accompanies hydration of K2 CO3, without effecting thermochemical performance. Na2 S and MgCl2 are salts with a higher storage density than K2 CO3 . Na2 S and MgCl2 face chemical degradation in thermochemical heat battery application. Abstract: Thermochemical materials K2 CO3, MgCl2 and Na2 S have been investigated in depth on energy density, power output and chemical stability in view of domestic heat storage application, presenting a critical assessment of potential chemical side reactions in an open and closed reactor concept. These materials were selected based on a recent review on all possible salt hydrates, within the frame of a thermochemical heat battery and considering recent advances in heat storage application. Judged by gravimetric and calorimetric experiments in operating conditions and worst-case-scenario conditions, K2 CO3 is recommended for both an open and closed system heat battery. The compound is chemically robust with a material level energy density of 1.28 GJ/m 3 in an open system and 0.95 GJ/m 3 in a closed system, yielding a power output of 283–675 kW/m 3 . Na2 S and MgCl2 on the other hand are chemically not robust in heat storage application, although having a higher energy density, output power and temperature in one cycle.